Effect of three anticoccidials on pharmacokinetics of tilmicosin in broiler chickens - El-Hewaity, Mohamed (International Journal of Pharmacology and Toxicology, 2016)
The disposition kinetic of tilmicosin (25mg/kg) was studied following oral administration alone, pretreated with amprolium (240 ppm), pretreated with diclazuril (2.5 ppm) and pretreated with toltrazuril (25 ppm) in broiler chickens. The serum tilmicosin concentrations were determined by microbiological assay technique using Bacillus subtilis (ATCC 6633) as the test organism. Following oral administration of tilmicosin, the disposition curve was best described by two-compartment open model. The maximum serum concentration (Cmax) was 1.90 ± 0.11, 1.27 ± 0.13, 1.50 ± 0.14 and 1.41 ± 0.11µg/ml for tilmicosin alone and in the presence of amprolium, diclazuril and toltrazuril, respectively. The elimination half-life (T0.5 (el)) was significantly decreased (5.28 ± 0.30, 5.88 ± 0.33, 6.03 ± 0.25 h, respectively) in amprolium, diclazuril and toltrazuril pretreated broiler chicken compared to tilmicosin alone (7.30 ± 0.41 h). The outcomes illustrated a significant decrease in the interval between doses in amprolium, diclazuril and toltrazuril pretreated broiler chicken compared to tilmicosin alone. Amprolium diclazuril and toltrazuril, resulted in a significance decrease in AUC (12.02 ± 1.14, 15.50 ± 1.26 and 14.56 ± 1.46 µg.h.ml-1, respectively) compared to tilmicosin alone (21.98±1.83 µg.h.ml-1). It is concluded that the administration of amprolium, diclazuril and toltrazuril before tilmicosin would altered its pharmacokinetic profile in broiler chicken.